Getreidekonjunktur und jüngerer Siedlungsausbau im südlichen Inneranatolien - Hütteroth, Wolf (ERDKUNDE, 1962)
The expansion of agriculture in Turkey has very considerably affected the settlement pattern, especially in Central Anatolia where the greatest changes have taken place. Most of the former steppe-pastures were claimed for arable during the period 1940-1960. Compared with the earliest statistics available for the smaller administrative units, i. e. 1937, cultivated land has increased in most cases by over 100 per cent., in particular in the basins and Neogenous plateaux of Central Anatolia, whereas economically the surrounding mountain regions have lagged behind considerably in comparison (Fig. 1). In order to elucidate the changes in appearance and structure resulting therefrom, the rural district of Konya was investigated, since it may in many respects be considered representative of Central Anatolia. Until about the beginning of this century this area was characterised by nucleated village settlement along the edge of the mountains, whereas in the open steppe country only a few large giant villages (agro-towns) were situated; their inhabitants, breeders of small livestock (viz. sheep and goats), lived during the summer in clans in the numerous surronding summer pastures (yayla). Opening up of the area by communication lines, availability of agricultural machinery and the possibility of marketing grain (Fig. 2) resulted in an upgrading of these temporary summer pasture settlements to hamlet-like permanent settlements, while the old agro towns either stagnated or shrunk altogether. This process brought out a reversal of the number-of-places-per-area ratio in comparison with the region of the old established farming villages at the mountain’s edge (Fig. 3) where only a limited intensification through improvement of irrigation was possible. (Irrigation there is not essential but merely advantageous.) Since recently Turkish cadastral maps have become available for a few villages (Figures 4-8) the pattern of field plots which dominates the present appearance of the former steppe pasture country makes it possible to follow the course of this process. Five village areas were investigated as examples for this purpose. This showed a twofold differentiation on the one hand between the earlier and the more recently developed parts of the village areas of the old villages, and on the other hand between the region of the old villages and that of the recently upgraded yayla settlements. Whereas the greater regularity of the recent block field complexes can be appreciated without difficulty this is not so with the regular strip field complexes, whose very existence does not appear to have been observed previously. They seem to occur only in the region of the old villages and are interpreted as the result of divisions of remaining pasture areas amongst the peasants after breaking the power of the ruling Aga families. This is thus a recent parallel development to the creation of strip field complexes by Arabian bedouins in Syria, a process also based on the idea of equality within a social group of similar interests. In the region of recent hamlet settlement the dominance of a number of clans could be maintained to a larger degree, thus the desire for the equal sharing out of land amongst a greater number of interested parties did not arise. A further reason for the absence of land fragmentation is the fact that in most cases each clan worked its arable blocks communally. The custom of divided in heritance, however, brings about in time claims by individuals to hypothetical fractional shares on the fields of the clan. Inheritance litigations, which have just started in order to achieve better rationalisation, lead in turn to both the disintegration of the economic function of a clan and the disruption of the two field system. In conclusion the question is discussed to what extent the methods of analysis of field patterns of the European school of settlement geography allow the gaining of a conception of the genesis of the Anatolian cultural landscape. The author is of the opinion that the ascertainably older elements of the field patterns allow at most a reconstruction of the conditions of the 19th century. The reason is that in view of the different legal conditions of the Near East the problem of the stability of field parcels still needs clarification.